Biosecurity Adoption on Cattle Farms in Indonesia - Lestari, Veronica S.; Nurani Sirajuddin, Sitti; Asnawi, Aslina (European Journal of Sustainable Development, 2014)
The aim of this study was to know biosecurity adoption on beef cattle farms. This research was conducted for a month at Barru regency, South Sulawesi province, which famous as one of beef cattle breeding villages in Indonesia. Sample was choosed through random sampling. Total sampel was 30 beef cattle farmers. Data were collected through observation and interview. Biosecurity measures consisted of 35 indicators which was grouped into 4 namely: management practice, sanitation, disease and disease prevention, and calf management. Each indicator was devided into two groups: adopt and not adopt. Data were analysed descriptively. The results revealed that 47.4% of beef cattle farmers have adopted biosecurity on their farms and was catagorized as a “partial adopter”. This percentage should be increased in order to increase meat production and food safety. Keywords: adoption, biosecurity, beef cattle, farmers